A mediação cultural em artes na Educação Infantil - Ferreira, Julliana Rizzia Silva (Universidade Federal de São Carlos, 2024)
The present work aimed to investigate the process of cultural mediation in arts in Early Childhood Education and its manifestation within the classroom, emphasizing its relevance for young children. In order to address the question-problem "how does cultural mediation with arts occur in Early Childhood Education?", the study's approach was grounded in understanding the concept of cultural mediation and its implications for educators in Early Childhood Education, guided by principles of freedom and respect regarding what is offered to children. In this context, concepts related to the child's right to choose within the cultural mediation framework were developed, considering the intersection between child and art. The study sought to comprehend which artistic expressions are present in Early Childhood Education and how teachers utilize various artistic languages, fostering simultaneous reflections on the autonomy of young children in the realm of arts. The research adopted a qualitative approach based on a bibliographic review. As a result, it was observed that cultural mediation in arts in Early Childhood Education is transformative when teachers take into account the choices, characteristics, and autonomy of young children in their diverse artistic expressions in the classroom. The central objective of the teacher when working with the arts in Early Childhood Education is to enable children to be creative and active in their learning processes, exploring their imagination capabilities and not being seen as mere spectators in the kindergarten.
Cultural mediation in arts in early childhood education
Keywords: Mediação cultural; Cultural mediation; Educação infantil; Early childhood education; Arte; Art; Formação docente; Teacher education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO